Transient detailed balance and product form for reaction networks. Issue 2 (3rd April 2017) - den Boer, Arnoud V.; Boucherie, Richard J.
ABSTRACT: This paper explores the boundary of the set of reaction networks that have an exact transient (truncated) multidimensional Poisson or product-form distribution for the number of particles of different types. Motivated by the birth–death process, we introduce the notions of transient detailed balance and delay functions, and use these notions to obtain the novel transient product-form distribution in a coagulation-fragmentation process for polymers with a tree-like structure from that of the pure coagulation process.